Integration of Motor Therapy in the Tahfidz Curriculum: An Effort to Improve Understanding of the Quran and Hadith in Madrasah Aliyah Students - Mimi Jamilah; Nilam Wahyu Syahputri (Edudeena : Journal of Islamic Religious Education, 2025)
This study examines the influence of motoric mastery on conceptual understanding in Islamic Education (PAI) learning and teaching in Islamic Senior High Schools (MA). Using a qualitative approach with a case study design, the study involved eight informants (four students and four teachers) who were purposely selected based on indications of motoric mastery through initial observation and the Developmental Coordination Disorder Questionnaire (DCDQ). Data collection was conducted through semi-structured interviews, participant observation during the process of recitation, memorization, and writing of Qur'anic verses, as well as analysis of assignment documents and evaluation reports. Data validity was guaranteed by triangulation of sources, methods, and time, as well as member checking. The results showed that fine motoric mastery hampered the precision of tajwid recitation, tafsir writing, and neuromuscular coordination, thus disrupting tadabbur and khusyu'. Gross motoric mastery led to rapid fatigue during group memorization and prayer demonstrations, which decreased spiritual motivation and the effectiveness of teacher role models. Miles and Huberman's interactive analysis reveals a causal relationship between motor, cognitive, and spiritual aspects of Islamic Education (PAI). These findings challenge the paradigm of religious education that separates the physical from the spiritual domains and urges the integration of motor therapy into the tahfiz curriculum and worship practices. Recommendations include routine motor screening, therapeutic calligraphy training, rhythmic prayer movements, and ergonomic classroom design. This holistic approach is expected to produce a comprehensive understanding of PAI, support the formation of noble characters, and become a lifelong investment in the afterlife